Performance of cryoprotectants, dehydration methods and tetrazolium test on the zygotic embryos of BGD coconut - Copeland-Gomes, Kicia Karine Pereira; Santos, Izulme Rita Imaculada; Almeida, Fabrício Tavares Cunha; Lédo, Ana da Silva (Scientia Plena, 2015)
The coconut (Cocos nucifera L.) is a palm found in the tropics, but has its origin in Asia. The in vitro germplasm banks offers multiple benefits and the long-term conservation meet those needs, but can also be used to keep recalcitrant and intermediate species. This study aims to test methods for dehydration and cryoprotection in long-term conservation of mature zygotic embryos of Brazil Green Dwarf (BGD), in liquid nitrogen at -196 ºC. Were used fruit zygotic embryos with 10 to 11 months old from a planting of BGD. Were evaluated different times of dehydration, cryoprotectant treatments and drying methods on embryos moisture using three methodologies. The methodology 3 promotes the lowest moisture content in zygotic embryos of BGD coconut accession. The mature zygotic embryos of BGD accession pre-treatment with cryoprotectant with sucrose 1.75 mol L-1 + glycerol 15% for 12 and 16 hours presented lower moisture content and larger viability by tetrazolium test.